Dinamika Pemikiran Ketatanegaraan dalam Fikih Siyasah Kontemporer - Rif'an Ilham; Muhammad Fardhannajmi; Subahan Subahan; Mohammad Aditya AB (Jurnal Teologi Islam, 2026)
This article examines the dynamics of constitutional thought in contemporary Islamic jurisprudence (fiqh siyasah), focusing on the normative foundations of the Qur'an and Hadith, the position of revelation and reason in Islam, and Ibn Taymiyyah's construction of the relationship between religion and the state. This research employs a library research method with a descriptive-analytical approach. The findings indicate that Islamic constitutional thought is grounded in the principles of tawhid, justice, trust (amanah), consultation (shura), and leadership accountability. Revelation functions as the supreme source of authority, while reason serves as an instrument of ijtihad. Constitutional matters belong to the sphere of ijtihadiyah, open to dynamic thinking and contextualization. Ibn Taymiyyah's thought affirms the integral relationship between religion and state through the realistic and contextual concept of siyasah shar'iyyah, remaining relevant to contemporary constitutional discourse.